Sacred Networks and Spiritual Resilience: Sustainable Management of Studenica Monastery’s Cultural Landscape - Nevena Debljović Ristić; Irena Kuletin Ćulafić (Land)
This study explores spiritual resilience as a mechanism for sustaining cultural landscapes, focusing on the UNESCO World Heritage Site of the Studenica Monastery (Serbia). By analysing the monastery’s sacred network, which includes monasteries, hermitages, and churches, the study demonstrates how material heritage (architecture, art), intangible practices (monastic life, liturgy, traditional crafts), and the natural environment (UNESCO MaB Golija–Studenica Biosphere Reserve) form a cohesive system of resilience. The concept of spiritual resilience is examined as a dynamic process that links sacred architectural structures and enduring religious practices with authentic land use preserved over centuries. We have utilised a methodological framework combining historical mapping, GIS viewshed analysis in spatial planning, and multidisciplinary data synthesis (historical, architectural, artistic, ecological, ethnographic) with resilience indicators aligned with the UNESCO’s Cultural Landscape approach. The findings reveal that Studenica’s sacred network operates as a coupled socio-ecological system. Spiritual practices, including annual processions and land stewardship rituals, have been identified as key factors in enhancing biodiversity conservation while mitigating land-use conflicts. Historical mapping has been used to highlight the overlap between sacred sites and protected ecological zones, reflecting traditional stewardship practices. By reframing heritage as an adaptive process where spirituality serves as a conduit between tradition and innovation, the study proposes replicable strategies for UNESCO sites worldwide. The concept of sacred landscapes as resilience hubs is furthered by alignment with SDG 11 (Sustainable Cities and Communities).